Membangun Karakter Masyarakat Bangsa Berbasis Teologi Gerakan Spiritual Baru - T. Safir Iskandar (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
The ideas for change can not be separated from the culture and civilization that originated from the paradigm that produces new creativities when faced with social stagnation. To solve the social problems, the sociological imagination ideas that exist and develop in the society should be incorporated so that they become a theological value system from the personal integrity of a community of nation. It is now the time for social imagination, as an idea, to be raised by an awareness to create and stimulate various changes in collective articulated discourses that deny the realities of social inequality established by the hegemony of any interests in the form of weakening the integrity of the nation in the name of the state. Theologically, for a successful and sustainable development of the nation there are six things to be considered: first, put the truth as the purpose of life. Second, the community of nations should not be restrained or restrain themselves both in thought and in social expression to the extent not contrary to the universal values. Third, justice must be incorporated into all aspects of society. Fourth, education must be provided to everyone. Fifth, critical thinking must be nurtured to respond to everything that goes into the community of nation both from within and from outside. And the last is the consistency and sincerity, dependability and sustainability of the five points mentioned above.